Comparative Performance of the MGISEQ-2000 and Illumina X-Ten Sequencing Platforms for Paleogenomics - Zhu, Kongyang; Du, Panxin; Xiong, Jianxue; Ren, Xiaoying; Sun, Chang; Tao, Yichen; Ding, Yi; Xu, Yiran; Meng, Hailiang; Wang, Chuan-Chao; Wen, Shao-Qing (Frontiers in Genetics, 2021)
The MGISEQ-2000 sequencer has been widely used in various omics studies, but the performance of this platform for paleogenomics has not been evaluated. We here compared the performance of MGISEQ-2000 with the Illumina X-Ten on ancient human DNA using four samples from 1750BCE to 60CE. We found there were only slight differences between the two platforms in most parameters (duplication rate, sequencing bias, θ, δS and λ). MGISEQ-2000 performed well on endogenous rate and library complexity, while X-Ten had a higher average base quality and lower error rate. Our results suggest that MGISEQ-2000 and X-Ten have comparable performance, and MGISEQ-2000 can be an alternative platform for paleogenomics sequencing.